Left atrial appendage exclusion in atrial fibrillation - Rozen, Guy; Margolis, Gilad; Marai, Ibrahim; Roguin, Ariel; Rahamim, Eldad; Planer, David; Heist, Edwin Kevin; Amir, Offer; Tahiroglu, Ilgar; Ruskin, Jeremy; Mansour, Moussa; Elbaz-Greener, Gabby (Frontiers in Cardiovascular Medicine, 2022)
Although oral anticoagulants (OACs) are first-line therapy for stroke prevention in patients with atrial fibrillation (AF), some patients cannot be treated with OACs due to absolute or relative contraindications. Left atrial appendage (LAA) exclusion techniques have been developed over the years as a therapeutic alternative for stroke prevention. In this paper, we review the evolution of surgical techniques, employed as an adjunct to cardiac surgery or as a stand-alone procedure, as well as the recently introduced and widely utilized percutaneous LAA occlusion techniques. Until recently, data on surgical LAAO were limited and based on non-randomized studies. We focus on recently published randomized data which strongly support an add-on surgical LAAO in eligible patients during cardiac surgery and could potentially change current practice guidelines. In recent years, the trans-catheter techniques for LAA occlusion have emerged as another, less invasive alternative for patients who cannot tolerate oral anticoagulation. We review the growing body of evidence from prospective studies and registries, focusing on the two systems which are in widespread clinical use nowadays: the Watchman and Amulet type devices. These data show favorable results for both Watchman and Amulet devices, setting them as an important tool in our arsenal for stroke reduction in AF patients, especially in those who have contraindications for OACs. A better understanding of the different therapeutic alternatives, their specific benefits, and downfalls in different patient populations can guide us in tailoring the optimal therapeutic approach for stroke reduction in our AF patients.